Late-stage functionalisation of peptides on the solid phase by an iodination-substitution approach - Werner, Marius; Pampel, Julius; Pham, Truc Lam; Thomas, Franziska (Chemistry - a European journal, 2022)
The functionalisation of peptides at a late synthesis stage holds great potential, for example, for the synthesis of peptide pharmaceuticals, fluorescent biosensors or peptidomimetics. Here we describe an on-resin iodination-substitution reaction sequence on homoserine that is also suitable for peptide modification in a combinatorial format. The reaction sequence is accessible to a wide range of sulfur nucleophiles with various functional groups including boronic acids, hydroxy groups or aromatic amines. In this way, methionine-like thioethers or thioesters and thiosulfonates are accessible. Next to sulfur nucleophiles, selenols, pyridines and carboxylic acids were successfully used as nucleophiles, whereas phenols did not react. The late-stage iodination-substitution approach is not only applicable to short peptides but also to the more complex 34-amino-acid WW domains. We applied this strategy to introduce 7-mercapto-4-methylcoumarin into a switchable ZnII responsive WW domain to design an iFRET-based ZnII sensor.
Online veröffentlicht am 14. Juni 2022
Gesehen am 19.12.2022